Future wireless networks: key issues and a survey (ID/locator split perspective). (1st January 2012) - So-In, Chakchai; Jain, Raj; Paul, Subharthi; Pan, Jianli
Future wireless networks (FWNs) are expected to be a convergence of different kinds of wireless technologies, such as cellular technologies, wireless local area networks (WLANs), wireless metropolitan area networks, wireless sensor networks, and traditional wired networks. The internet protocol (IP) will be potentially adopted as the common networking protocol for diverse networking technologies including the next generation of cellular networks using system architecture evolution (SAE). However, the IP architecture has several known challenges, such as mobility, multihoming, routing scalability, location privacy, path preference selection, etc. One of the greatest problems preventing the networks from overcoming these challenges is that the IP address is contextually overloaded, both as locators and identifiers. As a result, in this paper, we describe the issues of all-IP wireless networks, and survey recent proposals focusing on IP address overloading that can be applied to FWNs.